On modern beauty three paintings by Manet, Gauguin, and Cezanne - Brettell, Richard R. 1949-2020 (The J. Paul Getty Museum, 2019)
"An analysis of the notion of modern beauty that uses three Impressionist paintings in the collection of the J. Paul Getty Museum, Los Angeles, as the points of departure"--Provided by publisher
"This book is based on 'Toward a Modern Beauty: Manet, Gauguin, Cezanne,' the inaugural Getty Museum Distinguished Lecture, presented at the Getty Center in February and March 2016."
Keywords: Gauguin, Paul -- 1848-1903; Cézanne, Paul -- 1839-1906; Manet, Edouard -- 1832-1883; Frau -- Motiv; Malerei; Manet, Édouard / 1832-1883 / Criticism and interpretation; Gauguin, Paul / 1848-1903 / Criticism and interpretation; Cézanne, Paul / 1839-1906 / Criticism and interpretation; Cézanne, Paul / 1839-1906; Gauguin, Paul / 1848-1903; Manet, Édouard / 1832-1883; Impressionism (Art); Aesthetics, Modern / 19th century; Aesthetics, Modern; 1800-1899; Criticism, interpretation, etc